2014
DOI: 10.1104/pp.113.230383
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Stomatin-Like Protein Affects Mitochondrial Respiratory Supercomplex Organization      

Abstract: Stomatins belong to the band-7 protein family, a diverse group of conserved eukaryotic and prokaryotic membrane proteins involved in the formation of large protein complexes as protein-lipid scaffolds. The Arabidopsis (Arabidopsis thaliana) genome contains two paralogous genes encoding stomatin-like proteins (SLPs; AtSLP1 and AtSLP2) that are phylogenetically related to human SLP2, a protein involved in mitochondrial fusion and protein complex formation in the mitochondrial inner membrane. We used reverse gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…This would be consistent with the evidence that SLP-2 can dimerize (1) and may form homooligomeric complexes similar to PHBs (45). Indeed, SLP-2 was found to migrate in a high-molecular-weight complex by BN PAGE in rat liver, potentially as a homooligomeric complex (42), and a recent report has claimed that a plant homologue of Slp-2 in Arabidopsis thaliana may also be linked to RCS organization in plants (46). These reports corroborate our findings and, together with our data showing impaired RCS formation in both Slp-2 Ϫ/Ϫ MEFs and SLP-2-deficient T cells, point to a critical role for SLP-2 in RCS formation, one that is potentially conserved across different tissues and species.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This would be consistent with the evidence that SLP-2 can dimerize (1) and may form homooligomeric complexes similar to PHBs (45). Indeed, SLP-2 was found to migrate in a high-molecular-weight complex by BN PAGE in rat liver, potentially as a homooligomeric complex (42), and a recent report has claimed that a plant homologue of Slp-2 in Arabidopsis thaliana may also be linked to RCS organization in plants (46). These reports corroborate our findings and, together with our data showing impaired RCS formation in both Slp-2 Ϫ/Ϫ MEFs and SLP-2-deficient T cells, point to a critical role for SLP-2 in RCS formation, one that is potentially conserved across different tissues and species.…”
Section: Discussionsupporting
confidence: 75%
“…As we previously reported, our data show that the levels of PHBs present in the detergent (i.e., Triton X-100, digitonin, or dodecyl maltoside)-soluble fraction of mitochondrial lysates in the absence of SLP-2 are not different from control levels (5). Furthermore, SLP-2 does not seem to interact directly with RCS because experiments with plant mitochondria using complex I mutants lacking proper RCS associations showed that the migration pattern of a plant Slp-2 homolog is largely unchanged (46). It has also recently been reported that the Cox7a2l gene in several strains of mice, including C57BL/6J, carries a mutation that prevents the formation of complex IVcontaining RCS.…”
Section: Discussionmentioning
confidence: 99%
“…Successful preparation of outer membrane-free mitoplasts was confirmed by the absence of the voltage-dependent anion channel (VDAC, outer membrane) and the sensitivity of cytochrome c (intermembrane space) to degradation by proteinase K (Figure 1e). Both an MSL1-containing complex and the inner membrane protein SLP2 (Gehl et al, 2014) were detected in the mitoplast fraction treated with proteinase K (Figure 1e). The detection of an MSL1 band by anti-MSL1 antibodies, which recognise a short hydrophilic peptide sequence near the C-terminal end of MSL1 (see Experimental procedures), indicates that this region of the protein is in the matrix and is not accessible to proteinase K. In summary, MSL1 is an integral inner membrane protein of mitochondria with the C-terminus orientated towards the matrix.…”
Section: Msl1 Is An Integral Membrane Protein In the Mitochondrionmentioning
confidence: 99%
“…Central to the integration of signaling cues are mitochondria (Sweetlove et al, 2007), subcellular organelles that regulate its protein organization and composition, leading to metabolic adjustments associated with the synthesis of bioenergetic, redox, and secondary signaling molecules. On genetic (Zhang et al, 2012;Gehl et al, 2014), chemical (Obata et al, 2011;Lehmann et al, 2012;Ng et al, 2013aNg et al, , 2013b, or environmental stresses (for review, see Millar et al, 2011), mitochondrial impairment leads to the induction of alternative oxidase (AOX), a component of the mitochondrial respiratory chain. AOX oxidizes ubiquinol directly and reduces oxygen to water, bypassing the two coupling sites of complexes III and IV of the cytochrome electron transport chain, thus reducing the production of an electrochemical gradient used to generate ATP from ADP and inorganic phosphate by the ATP synthase complex.…”
mentioning
confidence: 99%